2018
DOI: 10.3389/fpsyg.2018.00884
|View full text |Cite
|
Sign up to set email alerts
|

Does Informal Caregiving Lead to Parental Burnout? Comparing Parents Having (or Not) Children With Mental and Physical Issues

Abstract: Introduction: Parenting a child with special needs (CSN) may be an important challenge. Previous research has highlighted an increased risk of parental burnout among parents caring for their CSN. Yet, these studies only focused on children with specific issues and did not consider the wide variety of CSN. There is thus a need to take a more global approach to assessing the impact of caring for a CSN on parental burnout. In addition, the impact on parental burnout of personality and parenting (dis)agreement nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 32 publications
2
69
0
14
Order By: Relevance
“…Participants were asked about their age, gender, type of family (single parenthood by choice or by circumstance, living with the children's father/mother, or blended family), level of education, work regimen, number of children, and for each child: gender, age, and whether the child suffered from a disease, disability, or behavioral/emotional/learning disorder (yes-no). If the parent answered “yes” for at least one child, he or she was asked to fill in a short questionnaire about the impact of having a child with special needs on his or her own life (see Gérain and Zech, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked about their age, gender, type of family (single parenthood by choice or by circumstance, living with the children's father/mother, or blended family), level of education, work regimen, number of children, and for each child: gender, age, and whether the child suffered from a disease, disability, or behavioral/emotional/learning disorder (yes-no). If the parent answered “yes” for at least one child, he or she was asked to fill in a short questionnaire about the impact of having a child with special needs on his or her own life (see Gérain and Zech, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Despite how often and urgently the autistic community discusses autistic burnout, the concept is almost completely absent from the academic and clinical literature. A literature search for autism and burnout produces publications on family, teacher, caregiver, peer, and other burnout related to caring for or being around autistic people, [3][4][5][6] but no studies on burnout in autistic people themselves. Two recent clinical articles reference autistic burnout as an issue to be considered, 7,8 and only a few other recent articles casually mention burnout as a potential consequence of poor social support or masking (camouflaging one's self to conform to social pressures) or include it as research priority.…”
Section: ''mentioning
confidence: 99%
“…Double-duty caregivers – being a formal and informal caregiver at the same time – are at higher risk of professional burnout than work-only caregivers (Häusler et al, 2017; DePasquale et al, 2018). In the same way, being an informal caregiver has been shown to increase the chances of parental burnout (Lindström et al, 2011; Gérain and Zech, 2018; Séjourné et al, 2018). The informal caregiving role thus seems to affect the caregiver’s other roles.…”
Section: Introductionmentioning
confidence: 96%
“…Emotional competencies have been found to play a role in preventing professional and parental burnout (Görgens-Ekermans and Brand, 2012; Mikolajczak et al, 2018) and identified as a promising target of intervention to reduce informal caregivers’ psychological distress (Weaving et al, 2014). More broadly, personality traits also seem to have an impact on subjective burden and informal caregiver burnout (Chiao et al, 2015; Gérain and Zech, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation